Effect of dietary organic selenium on muscle proteolytic activity and water-holding capacity in pork. (November 2016) - Calvo, L.; Toldrá, F.; Aristoy, M.C.; López-Bote, C.J.; Rey, A.I.
Abstract: This study evaluates the effect of dietary selenium (Se) supplementation source (organic, Se-enriched yeast; SY vs. inorganic, sodium selenite; SS), dose (0.2: L vs. 0.4: H mg/kg) and the combination of Se and vitamin E (VITE + SS) for 26 days on drip loss, TBARS, colour changes, myofibrillar protein pattern and proteolysis in pork. The lowest water losses were observed in the SY-H group when compared to the others. SY-H and VITE + SS groups presented lower myofibrillar protein hydrolysis/oxidation. VITE + SS supplementation also resulted in higher PRO, TRP and PHE content at days 2 and 7, whereas the SY group showed increased GLY and CAR and tended to have higher TAU and ANS at day 2. The myofibrillar fragmentation index was not modified by the dietary treatment; however, at day 8, it tended to be higher in groups supplemented with SeY and VITE + SS. The results of the present study might indicate a possible relation between muscle proteolysis and water loss. Highlights: The influence of selenium source and dose on muscle proteolytic activity was studied. Organic Se effectively increased WHC and post-mortem muscle proteolytic activity. Dietary vitamin E + Se supplementation was not as effective as organic Se in improving WHC. These results would confirm the relation between muscle proteolysis and WHC.